Preface: The 27th International Electronic Conference on Synthetic Organic Chemistry - Julio A. Seijas (Chemistry Proceedings)
This volume of Chemistry Proceedings assembles the papers presented at the 27th International Electronic Conference on Synthetic Organic Chemistry (ECSOC-27), held online on 15–30 November 2023, through the sciforum [...]